An experimental analysis of strain and stress for abs pattern developed by portable fdm machine used in direct investment casting - Mohamad, Elmy Johana; Ahmad, Muhammad Shukri; Marwah, Omar Mohd Faizan; Masood, Ibrahim (ARPN Journal, 2016)
Fewer reports regarding the portable FDM machine has encourage the study about the capability of the machine to be used as sacrificial master pattern in investment casting for small production of castings. This study presents an analysis of cracking on ceramic shell during burnout process to determine the maximum value of the hoop stress towards pattern itself and also hoop stress on ceramic shell. There are two types of the internal pattern structure whereby hollow and square in which built from portable Fused Deposition Modeling (FDM) technique with same thickness of ceramic shell. Strain gauge is viable tool in which was attached on patterns and ceramic shells to determine the maximum value of hoop stress during experimental burnout process. This experimental were conducted with variant temperature starting from 30°C until 150°C with increment of 5°C per minute. Moreover, experimental result shows that ABS P400 material strain was increased when subjected to increment of temperature and pressure. This phenomenon happened due to the different value of Coefficient Thermal Expansion (CTE) between the patterns and ceramic shell. In addition, experimental results show that the maximum hoops stress is higher on the square internal structure compared to the hollow internal structure. The hollow pattern experienced 40 % amount of reduction of strain compared to the square pattern. The observation was made that glass transition temperature, Tg between 70°C to 110°C. It was observed that the shell cracking happened on ceramic shell.